(3-4i)(5-6i)=

Simple and best practice solution for (3-4i)(5-6i)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3-4i)(5-6i)= equation:


Simplifying
(3 + -4i)(5 + -6i) = 0

Multiply (3 + -4i) * (5 + -6i)
(3(5 + -6i) + -4i * (5 + -6i)) = 0
((5 * 3 + -6i * 3) + -4i * (5 + -6i)) = 0
((15 + -18i) + -4i * (5 + -6i)) = 0
(15 + -18i + (5 * -4i + -6i * -4i)) = 0
(15 + -18i + (-20i + 24i2)) = 0

Combine like terms: -18i + -20i = -38i
(15 + -38i + 24i2) = 0

Solving
15 + -38i + 24i2 = 0

Solving for variable 'i'.

Factor a trinomial.
(3 + -4i)(5 + -6i) = 0

Subproblem 1

Set the factor '(3 + -4i)' equal to zero and attempt to solve: Simplifying 3 + -4i = 0 Solving 3 + -4i = 0 Move all terms containing i to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -4i = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -4i = 0 + -3 -4i = 0 + -3 Combine like terms: 0 + -3 = -3 -4i = -3 Divide each side by '-4'. i = 0.75 Simplifying i = 0.75

Subproblem 2

Set the factor '(5 + -6i)' equal to zero and attempt to solve: Simplifying 5 + -6i = 0 Solving 5 + -6i = 0 Move all terms containing i to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -6i = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -6i = 0 + -5 -6i = 0 + -5 Combine like terms: 0 + -5 = -5 -6i = -5 Divide each side by '-6'. i = 0.8333333333 Simplifying i = 0.8333333333

Solution

i = {0.75, 0.8333333333}

See similar equations:

| 5x^2+0x-125=0 | | 4x^3+5x^2-9x-18=0 | | -0.10(10)+0.25x=0.05(x-12) | | x+2i=4-yi | | 2i+i^2= | | x-15x+36= | | 4w=-5w-36 | | 25m^2+35m+10=0 | | -7t=-5t+2 | | 24x-3=-16x+27 | | 113-(5x+6)=5(x+6)+x | | 2w+12=7w-3 | | 2(2m-5)=4m+7 | | (-7+i)(9+i)= | | 43-(5x+60)=5(x+3)+x | | (x^2)-(2*x)+0.4=0 | | -8v-18=-2(4v+9) | | 3i-(16-4i)= | | x(55)+x(285)=1020 | | 2q+4=8 | | (7+4i)-(9-5i)= | | 5y-30=50 | | 25y-30=50-20y | | 5y^2+24y-5=0 | | f^2-6f+5=0 | | (7-4i)+(9+6i)= | | -6+5a=16+6a | | .25(x-1)+x=1 | | -4y=6y-8 | | 4a-2b-72=0 | | f(x)=-x^2+300x+6 | | 9z-6=9z-6 |

Equations solver categories